Climate Change Cooperation: A Case Study of SAARC - Sarim Akram Baacha (Research Parks Publishers, 2021)
South Asia is the region which is most vulnerable to the calamities of climate change. It is producing serious implication for the region like water, food and health insecurity. In addition to that global warming in the region is leading to the loss of human habitat and migration problems. The only threat that is deemed as credible and common among the SAARC countries is the climate change. Being highly prone to the appalling cataclysms of climate change that have resulted in to health, habitat, food and water security, the SAARC states had gone for cooperation from time to time in the past. To what extent the climate change cooperation will bring peace and stability in the region? In addition to that implications of climate change for south Asia and the steps taken by SAARC in order to cope with it will be discussed in the paper.